PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XI IPS 3 MAN 2 MAKASSAR - Muh Ilyas (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research is a type of classroom action research (action research) to improve the learning outcomes of Al-Quran Hadith students in class XII IPS 3 MAN 2 Makassar 2019/2020 by using discovery learning. This research was carried out in two cycles, namely cycle I and cycle II. These two cycles are a series of interrelated activities. The research subjects were 37 students in class XII IPS 3. The data obtained, namely student activities and learning outcomes, were analyzed using descriptive statistics. The results showed that activity in the positive aspects increased significantly from cycle 1 to cycle II, and the negative aspects decreased. Based on the learning results in cycle 1, it was proven that 78.3% had not yet completed and 21.6% had not yet completed. Based on the percentage of completeness, it has not reached 90% completeness, so the basis for continuing cycle II, cycle II is to perfect the reflection treatment from cycle I, while activities that measure character values have increased by 100% and learning outcomes in cycle II have reached 100% completeness. Shows that the application of discovery learning Matari, positive optimistic thinking, patiently facing tests and trials with a smile can improve the learning outcomes of students in class.